Pendampingan Tahsin Musykilatul Qira’at Imam Hafs dalam Membaca Al-Qur’an Untuk Masyarakat Malang Raya - Murdiono Murdiono; Moh. Fery Fauzi; Muhammad Amin (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
The purpose of this devotional activity is to provide assistance to the people of Malang Raya, especially the congregation of Ahmad Dahlan Karangploso Mosque in improving the ability to read musykilatul Qira'at in Reading the Qur'an according to imam hafs ashim history. The method of devotion with lectures and practice directly. The lecture method contains socialization to the community about qiro'at musykilatul. While the training is used by practicing directly the readings or verses that include Musykilatul verses according to the imam hafs. Stages of service implementation; (1) socialization for the delivery of materials to participants, (2) Implementation of musykilatul verse practices. (3) evaluation of activities. The output of this activity is the ability to read musykilatul verses of imam hafs properly.  The service program was held on July 20, 2020 at masjid KH. Ahmad Dahlan Karangploso. Participants who attended the event were about 25 people. The results of this devotional activity show that the community has a high motivation in learning the Qur'an and understanding the reading of musykilatul verses of imam hafs, as well as being able to practice the reading well and correctly which is shown by the ability to answer questions about musykilat verses.